Epidemiology and Phylogenetic Analysis of Viral Respiratory Infections in Vietnam - Lu, Lu; Robertson, Gail; Ashworth, Jordan; Pham Hong, Anh; Shi, Ting; Ivens, Alasdair; Thwaites, Guy; Baker, Stephen; Woolhouse, Mark (Frontiers in Microbiology, 2020)
Acute respiratory infections (ARIs) impose a major public health burden on fragile healthcare systems of developing Southeast Asian countries such as Vietnam. The epidemiology, genetic diversity and transmission patterns of respiratory viral pathogens that circulate in this region are not well characterized. We used RT-PCR to screen for 14 common respiratory viruses in nasal/throat samples from 4326 ARI patients from 5 sites in Vietnam during 2012-2016. 64% of patients tested positive for viruses; 14% tested positive multiple co-infecting viruses. The most frequently detected viruses were Respiratory syncytial virus (RSV, 23%), Human Rhinovirus (HRV, 13%), Influenza A virus (IAV, 11%) and Human Bocavirus (HBoV, 7%). RSV infections peaked in July to October, were relatively more common in children <1 year and in the northernmost hospital. IAV infections peaked in December to February and were relatively more common in patients >5 years in the central region. Coinfection with IAV or RSV was associated with increased disease severity compared with patients only infected with HBoV or HRV. Over a hundred genomes belonging to 13 families and 24 genera were obtained via metagenomic sequencing, including novel viruses and viruses less commonly associated with ARIs. Phylogenetic and phylogeographic analyses further indicated that neighbouring countries were the most likely source of many virus lineages causing ARIs in Vietnam and estimated the period that specific lineages have been circulating. Our study illustrates the value of applying the state-of-the-art virus diagnostic methods (multiplex RT-PCR and metagenomic sequencing) and phylodynamic analyses at a national level to generate an integrated picture of viral ARI epidemiology.